Children in Chinese art - Wicks, Ann Elizabeth Barrott, 1952- (University of Hawai'i Press, 2002)
Depictions of children have had a prominent place in Chinese art since the Song period (960-1279). Yet one would be hard pressed to find any significant discussion of children in art in the historical documents of imperial China or contemporary scholarship on Chinese art. Children in Chinese Art brings to the forefront themes and motifs that have crossed social boundaries for centuries but have been overlooked in scholarly treatises. In this volume, experts in the fields of art, religion, literature, and history introduce and elucidate many of the issues surrounding child imagery in China, including its use for didactic reinforcement of social values as well as the amuletic function of these works. The introduction provides a thought-provoking overview of the history of depictions of children, exploring both stylistic development and the emergence of specific themes. In an insightful essay, China specialists combine expertise in literature and painting to propose that the focus on children in both genres during the Song is an indication of a truly humane society. Skillful use of visual and textual sources from the Ming (1368-1644) and Qing (1644-1911) period explains children's games and the meaning of depictions of boys at play. Gender issues are examined in an intriguing look at mothers and children in woodblock illustrations to Ming versions of the classical text Lie ni juan. Depictions of the childhood of saints and sages from murals and commemorative tablets in ancient temples are considered. The volume concludes with two highly original essays on child protectors and destroyers in Chinese folk religion and family portraits and their scarcity in China before the nineteenth century. Contributors: Ellen B. Avril, Catherine Barnhart, Richard Barnhart, Terese Tse Bartholomew, Julia K. Murray, Ann Waltner, Ann Barrott Wicks.